SIFAT FISIKA TANAH PADA BERBAGAI TIPE PENGGUNAAN LAHAN DI SEKITAR TAMAN NASIONAL LORE LINDU (STUDI KASUS DESA TORO KECAMATAN KULAWI KABUPATEN SIGI SULAWESI TENGAH) - Rustam, Rustam; Umar, Husain; Yusran, Yusran (Universitas Tadulako, 2016)
The physics characteristics of soil haveÂ relation to the soil capability to store water, drainage, root penetration, air circulation, and soil substances binding.` Toro village is one of some villages around the Lore Lindu National Park, which area consist of some types of land uses, such as primary (Wana), Secondary (Pangale) and agroforestri (Pahawa Pongko) forest. The research was conducted on May up to the month of July 2015, that located around Lore Lindu National Park, Toro village, Kulawi subdistrict, Sigi district, Central Sulawesi. The research was done by doing survey of the location, deciding the spot of sample plot, taking sample of the soil in the laboratory. To determine the location, it was done purposively (purposive sampling) and took the sample of the soil in the depth of â‰¤ 30 cm. The data gathered from the laboratory then analized descriptively, describing the physics characteristics of the soil. The result of the research showed that the texture of the soil in the primary and secondary forest was clay and in the agroforestry was dusty clay. The permeability of the soil of the agroforestry land was 28,49 cm/hour, the secondary forest was 23,26 cm/hour and the primary forest was 8,39 cm/hour. The axis of the soil in the agroforestry land was 66,19%, the secondary forest was 58,41% and the primary forest was 48,78%. The soil Bulk Density of the agroforestry forest was 0,90 g/cm3, the secondary forest was 1,09 g/cm3, and the primary forest was 1.36 g/cm3.Keywords : Phyisics characteristics of the soil, land use, Lore Lindu National Park.